Retinoblastoma tumor suppressor protein is not a risk factor for the location of condyloma acuminatum among adults - Pratiwi Prasetya Primisawitri; ⁠Nurrachmat Mulianto; Endra Yustin Ellistasari; Eti Poncorini; ⁠⁠Harijono Kariosentono; Suci Widhiati; Brian Wasita; Novan Adi Setyawan; Muhammad Yurizar Yudhistira (Universa Medicina, 2025)
BackgroundCondylomata acuminata (CA) are sexually transmitted infections primarily caused by low-risk HPV types 6 and 11. Retinoblastoma protein (pRb) interacts with HPV oncoproteins, leading to destabilization, genomic instability, and carcinogenesis. This study aimed to determine whether variations in pRb expression and sexual orientation are risk factors of the anatomical location of CA lesions and to compare differences in pRb expression by sexual orientation. MethodsA cross-sectional study was conducted among 33 patients aged >18 years with clinically and histopathologically confirmed CA. Demographic data, pRb expression assessed via excision biopsy and immunohistochemistry, and relevant risk factors were collected. Statistical analyses including Simple and multiple binary logistic regression were used to analyze the data, with model fit assessed using the Hosmer–Lemeshow test. ResultsWeak pRb expression predominated in anal lesions (92.3%; p=0.018) and among homosexual/bisexual individuals (57.9%; p=0.031), while moderate expression was more common in genital lesions (66.7%; p=0.018) and heterosexual individuals (57.1%; p=0.011). Simple logistic regression  analysis showed that HIV status (OR=11.88; p=0.025), sexual orientation (OR=13.33; p=0.001), and moderate-to-strong pRb expression (OR=24.00; p=0.008; OR=12.00; p=0.048) were associated with lesion location. In the multivariate model, pRb expression was excluded due to multicollinearity. Sexual orientation remained the only independent predictor of lesion location (Adj OR=8.89; p=0.023), with heterosexual individuals more likely to present with genital lesions. ConclusionThe expression of pRb was not a risk factor of the anatomical location of CA, and differed between genital and anal CA. However, sexual orientation emerged as the dominant independent factor associated with lesion location.